2018
DOI: 10.1002/hpm.2643
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance in Myanmar: Knowledge, perceptions, and preferences of Social Security Scheme members and general adult population

Abstract: Summary Objective Our study explores the knowledge, perceptions, willingness to pay, and preferences of potential health insurance beneficiaries about health insurance in Myanmar. Methods Cross‐sectional survey data were collected among two samples: the general population and Social Security Scheme (SSS) member. Mann‐Whitney U test and independent sample t test were applied to compare the two samples. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…A study conducted in Uganda reported that about 34% of the studied population were not aware of health insurance. 1 Whereas, proportion of people having inadequate knowledge about health insurance was found to be high in countries such as India (46%), 5 Myanmar (66%) 3 and Hispanic American in the USA (70%). 19 Familiarity or awareness of the insurance schemes increases the utilisation of health insurance and subsequently help in healthcare uptake.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in Uganda reported that about 34% of the studied population were not aware of health insurance. 1 Whereas, proportion of people having inadequate knowledge about health insurance was found to be high in countries such as India (46%), 5 Myanmar (66%) 3 and Hispanic American in the USA (70%). 19 Familiarity or awareness of the insurance schemes increases the utilisation of health insurance and subsequently help in healthcare uptake.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…1 People living in the LMICs rely majorly on out-of-pocket payments as the prime source for managing healthcare expenses, that results in a massive demand for services and financial burden of households (usually catastrophic), which in turn leads to impoverishment. [1][2][3][4][5] It is projected that every year approximately 150 million people experience financial catastrophe, by spending more than 40% on health expenses other than food. 6 Families generally spend more than 10% of the household income on illness-related expenses, due to which other household expenses are affected.…”
Section: Introductionmentioning
confidence: 99%
“…OOP, out-of-pocket. Sources: World Health Organization (2018); World Bank (2018); Myint et al (2018); and Sydavong et al (2019).…”
Section: Health Financing In the Lower Mekong Regionmentioning
confidence: 99%
“… 16 In Sweden, a gap has been found between public expectations and medical attention resources, making it even more important to have clarity on who must be accountable for resource allocation in public healthcare. 17 Research about citizen’s opinions in developing countries has focused primarily on willingness to pay for health insurance, for example, Myanmar, 18 Ethiopia, 18 and Uganda. 18 More related to our work is the study of the associations between satisfaction with the health care system and its determinants in Armenia 19 ; public attitudes toward health insurance and its reform in Croatia 20 ; the analysis of public opinion on universal health care coverage on health care affordability and financing issues in South Africa 21 ; and the study of attributes of health insurance benefit packages in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…17 Research about citizen's opinions in developing countries has focused primarily on willingness to pay for health insurance, for example, Myanmar, 18 Ethiopia, 18 and Uganda. 18 More related to our work is the study of the associations between satisfaction with the health care system and its determinants in Armenia 19 ; public attitudes toward health insurance and its reform in Croatia 20 ; the analysis of public opinion on universal health care coverage on health care affordability and financing issues in South Africa 21 ; and the study of attributes of health insurance benefit packages in Iran. 21 This article aims to gain a deeper understanding of attitudes toward health financing through the application and analysis of a scale developed especially for this goal.…”
Section: Introductionmentioning
confidence: 99%